A Qualitative Assessment of the Multimodal Passenger Transportation System Response to COVID-19 in New York City. Issue 4 (April 2023) - Abreu, Luis; Conway, Alison
This paper presents a qualitative analysis of transportation system changes that occurred in New York City (NYC) from the beginning of the COVID-19 pandemic until the city began its first phase of reopening in June 2020. The study was conducted by tracking publicly available transportation-related news articles and publications, 1) to capture key issues and challenges and 2) to identify changes in policies, services, and infrastructure that occurred in response across five passenger transportation modes: public transit; taxis; ridesharing; personal driving; and cycling and micromobility. Results were assessed to identify common issues and interactions between modes. The paper concludes with key lessons learned from this event, and recommendations for future policy.